2009
DOI: 10.1080/09638230701879094
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and associated factors following cerebrovascular accident among Nigerians

Abstract: Background: Much has been written on post stroke depression in the last 10 years in developed countries. However little is known about this important condition in this environment, thus the need for this study. Aims: This study intends to estimate the prevalence of post stroke depression (PSD) and identify other associated factors. Methods: One hundred and eighteen stroke survivors, managed at a Nigerian Teaching Hospital (mean post stroke survival duration ¼ 11 months) were compared with 118 hypertensive cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
2
23
0
2
Order By: Relevance
“…Further, patients who were not grouped had a higher education level. Education level has been reported to be associated with depression after stroke in only a few studies [19,38] and is not regarded as a major predictor of PSD [1]. Although no difference was found regarding the education level among the non-depressed, early-onset, and late-onset PSD groups, the possibility of a bias due to the discrepancy between the education level of study patients and dropouts cannot be ruled out.…”
Section: Discussionmentioning
confidence: 53%
“…Further, patients who were not grouped had a higher education level. Education level has been reported to be associated with depression after stroke in only a few studies [19,38] and is not regarded as a major predictor of PSD [1]. Although no difference was found regarding the education level among the non-depressed, early-onset, and late-onset PSD groups, the possibility of a bias due to the discrepancy between the education level of study patients and dropouts cannot be ruled out.…”
Section: Discussionmentioning
confidence: 53%
“…Only a handful of studies have included patients with aphasia in their sample with mixed results as to the effect of aphasia on developing PSD (Berg et al, 2003; Kauhanen et al, 2000; Kellermann et al, 1999; Nys et al, 2005). Relatedly, stroke severity and neurological impairment including hemiparesis have been associated with depression (Fatoye et al, 2009; Vataja et al, 2001). …”
mentioning
confidence: 99%
“…12,13,16,17 Co mparison adults without stroke: Rates higher in stroke. 20,21,23,29,31,32 Rates not signifi cantly different. 31 He adache/migraine pain: 3%-18%.…”
Section: Search Criteriamentioning
confidence: 90%
“…7,10,20,21,25,27,28,31 Depression was more prevalent in stroke populations than in nondisabled control populations. 20,21,23,29,31,32 Pain Twelve studies reported on the overall prevalence of pain. Half of these studies reported pain prevalence in the range of 26% to 50%, and 5 studies reported lower pain prevalence of 25% or less.…”
Section: Search Criteriamentioning
confidence: 95%
See 1 more Smart Citation